Genomic profiling of endometrial cancer and relationship with volume of endometrial cancer disease spread - Stephanie A. Sullivan; Gabriel Hawkins; Xiobai Zhao; Heejoon Jo; Neil Hayes; Xiaoyan Deng; Dipankar Bandyopadhyay; Victoria L. Bae-Jump; Emma C. Rossi (Gynecologic Oncology Reports, 2021)
Objectives: Lymph node (LN) metastasis and genomic profiles are important prognostic factors in endometrial cancer (EMCA). However, the prognostic significance of low volume metastasis found in sentinel lymph nodes (SLN) is unknown. We sought to determine if genomic mutations were associated with metastatic volume. Methods: Surgically staged women with EC who were enrolled in both a SLN clinical trial and tumor sequencing protocol were eligible. Relevant targets were enriched by a custom designed Agilent SureSelect hybrid capture enrichment library using standard protocols. Three specific gene mutations were evaluated, TP53, PTEN and PIK3CA in the primary tumor of patients with LN negative, LN positive and ITC disease. Results: 42 patients were eligible; of these, 7 (16.7%) had ITC only and 7 (16.7%) had micrometastatic or macrometastatic (LN positive) disease. No differences were seen in TP53, PIK3CA or PTEN between groups. All ITC patients with TP53 mutations were of non-endometrioid histology (2/7). Deeper myometrial invasion and lymph vascular space invasion were more likely to occur in the LN positive group (p < 0.01 for both). No patients with ITC had a recurrence in a median 67.7 months of follow-up since surgery. Conclusions: This pilot investigation did not identify differences between frequency of PIK3CA, PTEN or TP53 mutations in tumors and volume of LN metastasis. Low number of ITC limited the ability to detect genomic differences, however mutations appeared to align with expected histology. More work is needed to define the relationship between genomic mutations, histology, ITC, and prognosis.